Effects of leguminous green manure-crop rotation on soil enzyme activities and stoichiometry - Liu, Meixia; Hu, Zonghao; Fan, Yi; Hua, Bin; Yang, Wei; Pang, Shuang; Mao, Rong; Zhang, Yang; Bai, Keyu; Fadda, Carlo; De Santis, Paola; Bergamini, Nadia; et al. (Oxford University Press, 2024)
As a crucial strategy for sustainable agricultural production, green manure–crop rotation can regulate soil nutrient cycling and decrease the reliance on nitrogen fertilizers. However, we still lack a comprehensive understanding of the changes in soil eco-enzyme activities, microbial metabolism and nutrient limitations caused by leguminous green manure–crop rotation. Here, we conducted field experiments of leguminous green manure–crop rotation across China to analyze soil extracellular enzyme activities, specifically β-glucosidase (BG), N-acetyl-β-d-glucosaminidase (NAG), leucine aminopeptidase (LAP) and acid phosphatase (AP). The study revealed that long-term green manure–crop rotation increased carbon and nitrogen accumulation in farmland, with a significant average increase of 20.1% and 36.4% in BG, AP enzyme activities in topsoil, while showing a decrease in ln(NAG + LAP):ln(AP) ratios. The ratios of ln(BG):ln(NAG + LAP) and ln(NAG + LAP):ln(AP) in soil across various regions were typically below 1:1, indicating that soil microbial activity is more constrained by nitrogen and phosphorus nutrients rather than by carbon. Precipitation, temperature, soil total carbon (TC) and total nitrogen (TN) were identified as key environmental factors for extracellular enzyme activities and stoichiometric ratios. Our study highlights that the green manure–crop rotation alleviates nitrogen limitation while enhancing phosphorus limitation, and is closely related to the accumulation of TC and TN in the soil.